Mastering Spring Framework Fundamentals - Speake, Matthew (Packt Publishing, 2020)
Give a boost to your development career by mastering Spring framework concepts About This Video Get to grips with the Spring framework Develop a solid understanding of Spring containers and their applications Become well-versed with Spring MVC and web application development using Spring In Detail By promoting excellent coding practices and speeding up development time, the Spring framework has proved its metal in the world of software development and is now the most in-demand skill for Java developers. If you're looking to get to grips with Spring and the important techniques and best practices, then this is the right course for you. You'll start by configuring a project's dependencies to use Spring. Next, you'll understand the functionality and application of dependency injection and inversion of control in Spring. As you progress, you'll manage application properties and state using Spring property management and learn how to apply profiles in Spring. You'll also find out how to use proxies for making service methods transactional. Moving ahead, you'll get to grips with lifecycle and callback interfaces and the events needed to integrate and access lower-level components of the Spring container. Later, you'll get an overview of Spring JDBC and uncover techniques to work with databases. Finally, you'll delve into web application development with Spring. By the end of this course, you'll be able to confidently work with existing Spring applications and build your own projects from the ground up.